Preliminary results of the solid-state C-13 NMR study of Mongolian coals: Implications for oil and gas potential and liquefaction reactivity - Erdenetsogt, Bat-Orshikh; Ko, Yoon-Joo; Lee, Insung (Geological Issues, 2023)
Chemical structures of five coals from Mongolia were studied using solid-state C-13 NMR and oil and gas potential as well as yields of liquefaction products of the coals have been predicted. Pennsylvanian ZG, Upper Permian TT and Lower-Middle Jurassic AT-5 coals might have more potential for gas due to abundant aliphatic and aromatic CH3 carbons. Lower-Middle Jurassic KH coal probably has more potential for oil because of its increased CH2 content. Lower Cretaceous SO-3 coal may have more potential for gas, but significant amount of non-hydrocarbon gases could also be generated simultaneously. The prediction of yields of liquefaction product shows that ZG, TT and AT-5 and KH coals could yield similar hydrocarbon gas, oil and residue. Cretaceous SO-3 coal is predicted to give the lowest yields of oil, hydrocarbon gas and residue compared with others. KH sample has the highest oil yield due to its high content of CH2. Keywords: coal, petroleum potential, NMR, Mongolia